The Focal Press companion to the constructed image in contemporary photography - Massoni, Anne Leighton; Shindelman, Marni (Focal Press companion, 2019)
This compendium examines the choices, construction, inclusions and exemptions, and expanded practices involved in the process of creating a photograph. Focusing on work created in the past twenty-five years, this volume is divided into sections that address a separate means of creating photographs as careful constructs: Directing Spaces, Constructing Places, Performing Space, Building Images, and Camera-less Images. Introduced by both a curator and a scholar, each section features contemporary artists in conversation with curators, critics, gallerists, artists, and art historians. The writings include narratives by the artist, writings on their work, and examinations of studio practices. This pioneering book is the first of its kind to explore this topic beyond those artists building sets to photograph.